An Analysis of Trap Monopoly Game in Teaching Speaking - Fandy Nur Hidayat (International Journal of English Linguistics, Literature, and Education (IJELLE), 2021)
The aims of these research were to know the process of teaching speaking by using trap monopoly game at XI TKJ Grade of Students of SMK Muhammadiyah 2 Sukoharjo, and to describe the implementation of using trap monopoly game itself.This research conducted by the researcher using qualitative method..The data was collected by virtual observation, interview, questionnaire, and documentation. The researcher analyzed the data by interactive model from Miles and Huberman (1984). The result of this research were : First, the process of teaching speaking by using trap monopoly game in teaching speaking. On pandemic of Covid-19, the teacher used virtual learning by zoom meeting application. Second, the implementation of teaching speaking by using trap monopoly game as the learning media on vocabulary, narrative and recount text, procedure text, giving opinion materials.The strenghtness of using the trap monopoly game was helping the teacher in learning activity, more interesting and as the alternative teaching speaking media. Moreover,using of trap monopoly game was helping the students more active and confidence to speak english. The weakness of using trap monopoly game as the teaching media was the teacher must prepare the teaching media previously, E-learning process was less smoothly because the internet signal was bad